NEGOTIATION OF MEANING: STUDENTS’ AWARENESS OF THEIR MISTAKES IN USING ENGLISH FOR THE SECONDARY SCHOOL LEVEL - Ferayani Ulrica (Universitas Teknokrat Indonesia, 2020)
In traditional classes, teachers teach grammar in a deductive way with meaningless activities. The activities do not emphasize the uses of English in real life and lack of communication among teachers and students. Language awareness might give the students a challenge to pose questions and encourage them to explore themselves on how language works. The teachers might be able to encourage the students to participate to lead them to get communicative skills by using negotiation of meaning. This article is intended to explore and analyze the students’ mistakes when negotiating meaning in the language learning process. The qualitative descriptive research was employed in this study with 33 students in senior high school as the subjects of the research. The data were from the students’ interviews and recordings. The finding revealed that the students produced mistakes in grammar, pronunciation, and vocabulary. It showed that the extent of the students’ awareness in responding to a mistake in the negotiation of meaning was low. It was only 16 incorrect utterances that might be corrected by the students. It was divided into two sides, willingness and unwillingness to correct. Factors were affecting the students not to be aware during interaction such as focusing on meaning, the same proficiency level, and condition of the class.